2007
DOI: 10.1185/0300799007x219544
|View full text |Cite
|
Sign up to set email alerts
|

Short-term economic impact of body weight change among patients with type 2 diabetes treated with antidiabetic agents: analysis using claims, laboratory, and medical record data

Abstract: Weight loss significantly reduced diabetes-related costs. Controlling for baseline factors in the regression model, the 1-year total health care cost following 1% weight loss (or gain) was $213 cost decrease (or increase). Diabetes-related cost did not appear to be associated with weight gain. Economic benefit of weight loss was evident among type 2 diabetic patients on antidiabetic therapy, especially among obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 34 publications
4
59
0
1
Order By: Relevance
“…Nevertheless, a vicious circle may ensue with antidiabetic agents, with increases in weight resulting in a secondary increase in insulin resistance, which subsequently necessitates an increase in medication requirements to maintain glucose homeostasis. Weight gain with antidiabetic agents can pose a significant psychological barrier to the initiation or intensification of treatment, leading to patient noncompliance [48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a vicious circle may ensue with antidiabetic agents, with increases in weight resulting in a secondary increase in insulin resistance, which subsequently necessitates an increase in medication requirements to maintain glucose homeostasis. Weight gain with antidiabetic agents can pose a significant psychological barrier to the initiation or intensification of treatment, leading to patient noncompliance [48].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a vicious circle may ensue with antidiabetic agents, with increases in weight resulting in a secondary increase in insulin resistance, which subsequently necessitates an increase in medication requirements to maintain glucose homeostasis. Weight gain with antidiabetic agents can pose a significant psychological barrier to the initiation or intensification of treatment, leading to patient noncompliance [48].Given the strong association between excess weight and type 2 diabetes, the prevention of weight gain in people with diabetes, as well as in individuals with impaired glucose tolerance (IGT), should be a cardinal focus in treatment strategies. In this review, the multifactorial and progressive nature of type 2 diabetes is discussed with a view to understanding the aetiology and treatment of diabetes and associated obesity, leading to an examination of the range of antidiabetic therapeutics available to treat it.…”
mentioning
confidence: 99%
“…The Food Standards Agency in the UK has calculated that 42 000 lives could be saved by increasing fruit and vegetable consumption to the five-a-day target (from about 3?5 portions) and 20 000 lives by reducing salt intake (from 9 to 6 g/d) (7) . In the USA, 1 % individual weight loss could result in an annual saving of $US 213 per diabetes patient (8) .…”
mentioning
confidence: 99%
“…However, studies have investigated the direct relationship of Body Mass Index (BMI)-based excess weight with the use of medicines and the need of hospitalization [18,19], and such studies found that BMI affects healthcare costs [20,21]. Recently, an extensive review of 32 original articles published between 1990 and 2009 [22] found that the direct healthcare costs of obese individuals (BMI ≥30kg/m 2 ) are approximately [23] found that a 1.0% reduction in body weight was directly associated with a 3.6% reduction in the costs of treating diabetics. Our results show that higher waist cicumfernce is associated with higher costs, regardless of BMI.…”
Section: Discussionmentioning
confidence: 99%